Configurations of human-centered AI at work: seven actor-structure engagements in organizations - Wilkens, Uta; Lupp, Daniel; Langholf, Valentin (Frontiers in Artificial Intelligence, 2023)
Purpose -The discourse on human-centricity of AI at work needs a contextualization. The aim of this paper is to distinguish prevalent criteria of human-centricity for AI applications in the scientific discourse and to relate them to the work contexts for which they are specifically intended. This leads to configurations of actor-structure engagements fostering human-centricity in the workplace.Theoretical foundation -The paper applies configurational theory to sociotechnical systems' analysis of work settings. The assumption is that different approaches for enhancing human-centricity co-exist in dependence on the stakeholders who are in charge of their application.Method -The exploration of criteria indicating human-centricity and their synthesis to configurations is based on a cross-disciplinary literature review following a systematic search strategy and a deductive-inductive qualitative content analysis of 101 research articles.Results -The paper outlines eight criteria of human-centricity, two of them facing challenges of human-centered technology development (trustworthiness, explainability), three challenges of human-centered employee development (prevention of job loss, health, and human agency & augmentation), and three challenges of human-centered organizational development (compensation of systems' weaknesses, integration of user-domain knowledge, accountability & safety culture). Configurational theory allows a contextualization of these criteria from a higher order perspective and leads to seven configurations of actor-structure engagements in terms of engagement for (1) data and technostructure, (2) operational process optimization, (3) operators' employment, (4) employees' well-being, (5) proficiency, (6) accountability, and (7) interactive cross-domain design. Each has one criterion of human-centricity in the foreground. Trustworthiness does not build an own configuration but is proposed to be a necessary condition in all seven configurations.Discussion -The paper leads to a contextualization of the overall debate on human-centricity and allows to specify stakeholder-related engagements and how these complement each other. This is of high value for practitioners bringing human-centricity to the workplace and allows to compare which criteria are considered in transnational declarations, international norms and standards or company guidelines.